2018
DOI: 10.1002/jrs.5502
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐enhanced inelastic scattering by 2D and 3D superlattices made of silver nanocrystals

Abstract: The lattice dynamics of natural crystals, artificial superlattices, or self‐organized nanocrystals intimately mix confinement, coupling, periodicity, and dissipative effects. The low wavenumber vibrational response of the new class of nanomaterials called “supercrystals” does contain relevant information concerning finite size effects on atomic movements inside each nanocrystal, mechanical coupling between adjacent nanocrystals, coherent behavior of the total assembly due to its superperiodicity, and finally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…These nanoparticles have been identified as having potential applications in radiation detection and cancer treatment because of the fact that they can be activated by light, X‐rays, ultrasound, and microwave radiation to produce reactive oxygen species. Courty et al [ 93 ] described their work on plasmon‐enhanced inelastic scattering by 2D and 3D superlattices made of silver nanocrystals. They showed that for low particles diameter (≲5 nm), deviations from the continuum elastic approximation occur and that the vibrational response is more sensitive to atomic arrangements and surface effects inside the nanocrystals than to spatial coherence effects between them.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…These nanoparticles have been identified as having potential applications in radiation detection and cancer treatment because of the fact that they can be activated by light, X‐rays, ultrasound, and microwave radiation to produce reactive oxygen species. Courty et al [ 93 ] described their work on plasmon‐enhanced inelastic scattering by 2D and 3D superlattices made of silver nanocrystals. They showed that for low particles diameter (≲5 nm), deviations from the continuum elastic approximation occur and that the vibrational response is more sensitive to atomic arrangements and surface effects inside the nanocrystals than to spatial coherence effects between them.…”
Section: Nanomaterialsmentioning
confidence: 99%